(3JMaI Gdedhc hGdQZGFH deG aj GdHQ hGdHMQ ef GdYLGFH hGdZQGFHs - (3fhQ GdOjf CMeO Hf Ydj Hf CMeO GdeMdi GdTGaYj GdeYQha HGHf RfHd GdQeGd,J (B980 (3g` s ((3Rjf GdOjf GdWQGHdSi s)
(3ChdgG (B:s
(3GYde jG BNQ habfG Gddg Gffi deG GfgjJ cJGHi GdeSei HeNJUQ GdLZQGajG s
(3BNQgG (B:s
(3hJacQ ajg aEfg Yde jgOi Edi s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B180s
(3eUOQ GbJfGA GdCUd (B:s
(3HdOjI GdCScfOQjI (B(3617 (3L(B) s
Keywords: (3GdLZQGajG h GdHdOGfs